Recognizing Amino Acid Chirality with Surface-Imprinted Polymers Prepared in W/O Emulsions - Min Jae Shin; Young Jae Shin; Seung Won Hwang; Jae Sup Shin (International Journal of Polymer Science)
A molecularly imprinted polymer was prepared by a surface molecular imprinting technique in water-in-oil (W/O) emulsion. In this technique, the solid polymer, which is molecularly imprinted at the internal cavity surface, is prepared by polymerizing W/O emulsions consisting of a water-soluble imprinted molecule, a functional host molecule, an emulsion stabilizer, and a crosslinking agent. Dioleoyl phosphate was used as an emulsion stabilizer, and this compound also acted as a monomer and a host functional group in the imprinted cavity. Divinylbenzene was used as a crosslinker. Tryptophan methyl ester and phenylalanine methyl ester were used as the target template materials. These imprinted polymers exhibited enantiomeric selectivity in absorption experiments, and the maximum separation factor was 1.58. The enantiomeric selectivity with tryptophan methyl ester was higher than that with phenylalanine methyl ester.